Secondary distribution of injecting equipment obtained from needle and syringe programmes by people injecting image and performance enhancing drugs: England and Wales, 2012-15. (1st February 2019) - Glass, Rachel; Hope, Vivian D.; Njoroge, Jacquelyn; Edmundson, Claire; Smith, Josie; McVeigh, James; Parry, John; Desai, Monica
Highlights: Secondary distribution of equipment from needle and syringe programs (NSPs) is common among IPED injectors. Overall, 154 people collected equipment for 639–1, 569 people injecting image and performance enhancing drugs (IPEDs). Those also injecting psychoactive drugs were more likely to collect for others. Many of those injecting IPEDs are likely not in direct contact with NSPs. Innovative harm reduction approaches using online platforms and peers are needed. Abstract: Background: People who inject image and performance enhancing drugs (IPEDs) are often the largest group using needle and syringe programmes (NSPs) in the UK. NSP providers report these clients repeatedly collecting large amounts of equipment for others. The extent of secondary distribution of injecting equipment is unknown. Methods: Data from national surveillance of people injecting IPEDs were used. Participants completed a questionnaire and provided a dried-blood spot sample. Data from two biennial surveys was combined; repeat participants were excluded. Self-reported data was used to explore the extent of secondary distribution. Results: Of the participants, 87% (467) reported NSP use; median age was 31 years; 98% were male. A third (34%, 157) reported collecting equipment for others. Of those collecting for others, 154 reported how many people they had collected for: 55% had collected for one person, 27% for 2–9 people, 5% for 10–19 and 13% for 20 or more (no difference by psychoactive drug use). Those vaccinated for hepatitis B were more likely (22% [15/68] vs 6% [5/86], p = 0.003), and those reporting redness/swelling at an injection site were less likely to collect equipment for at least 20 others (8% [8/106] vs 25% [12/48], p = 0.003). Overall, 154 people collected equipment for 639-1569 people injecting IPEDs. Conclusions: Secondary distribution of injecting equipment is common among those injecting IPEDs and using NSPs. Whilst not allowing for rotational collection within groups, our analysis suggests that many of those injecting IPEDs are not in direct contact with NSPs. Innovation approaches for harm reduction interventions are needed.